EmoTan: enhanced flashcards for second language vocabulary learning with emotional binaural narration - Shogo Fukushima (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract We report on the design and evaluation of a flashcard application, enhanced with emotional binaural narration to support second language (L2) vocabulary learning. Typically, the voice narration used in English vocabulary learning is recorded by native speakers with a standard accent to ensure accurate pronunciation and clarity. However, a clear but monotonous narration may not always aid learners in retaining new vocabulary items in their semantic memory. As such, enhancing textual flashcards with emotional narration in the learner's native language can foster the retention of new L2 words in episodic rather than semantic memory as greater emotive expression reinforces episodic memory retention. We evaluated the effects of binaural emotive narration with traditional textual flashcards on L2 word retention (immediate and delayed) in laboratory experiments with native Japanese-speaking English learners. Our results suggest that the learners were able to retain approximately 60% more L2 words long-term with the proposed approach compared to traditional flashcards.